2015
DOI: 10.1016/j.aqpro.2015.02.148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Onsite Sanitation System on Groundwater in Different Geological Settings of Peri Urban Areas

Abstract: Pit Latrines and Septic tanks are common modes of onsite sanitation commonly used in India. These modes of onsite sanitation are becoming source of Groundwater contamination. The chemical contaminants and pathogenic bacteria released from these onsite sanitation systems are in filtered into the surrounding groundwater sources through soil media and causing the threat. This threat is more severe in dense habitation where both onsite sanitation and drinking water resources are spaced very close. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…Pit latrines and sceptic tanks are common types of on-site sanitation facility in rural areas of India and are sources of groundwater contamination. A study conducted in peri-urban areas of India found seepage of sewage into groundwater from improperly designed rural sanitation facilities (Shivendra and Ramaraju 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pit latrines and sceptic tanks are common types of on-site sanitation facility in rural areas of India and are sources of groundwater contamination. A study conducted in peri-urban areas of India found seepage of sewage into groundwater from improperly designed rural sanitation facilities (Shivendra and Ramaraju 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At a research site in India marked by shallow water levels and broken rock aquifers, high concentrations of faecal coliforms were found in domestic wells located near pit latrines and septic tanks. During the rainy season, rotaviruses are transported by groundwater flow in the upper part of the ground, whereas travel in the dry season is more likely to be caused by directly contaminated surface water [18]. The same condition is likely to occur in this study.…”
Section: Resultsmentioning
confidence: 58%
“…These systems must be periodically emptied (or replaced, in the case of some pit latrines), and safe disposal and treatment of waste may be costly for users and difficult to carry out in high-density informal settlements. This often leads to poor management of pit latrines and septic tanks, which can contribute to contamination of the surrounding environment (e.g., groundwater), particularly during high rainfall events [10,11]. Small and medium-sized cities face particular constraints in providing adequate wastewater treatment and faecal sludge management capacities due to more limited urban management capacity and lower revenues.…”
Section: Poor Access and Dysfunctional Systemsmentioning
confidence: 99%